Fluorescein-guided surgery for high-grade glioma resection: a five-year-long retrospective study at our institute - Xi, Chen; Jinli, Sun; Jianyao, Mao; Yan, Chen; Huijuan, Li; Zhongjie, Shi; Zhangyu, Li; Liwei, Zhou; Yukui, Li; Sifang, Chen; Guowei, Tan (Frontiers in Oncology, 2023)
Objective: This study investigates the extent of resection, duration of surgery, intraoperative blood loss, and postoperative complications in patients with high-grade glioma who received surgery with or without sodium fluorescein guidance. Methods: A single-center retrospective cohort study was conducted on 112 patients who visited our department and underwent surgery between July 2017 and June 2022, with 61 in the fluorescein group and 51 in the non-fluorescein group. Baseline characteristics, intraoperative blood loss, surgery duration, resection extent, and postoperative complications were documented. Results: The duration of surgery was significantly shorter in the fluorescein group than in the non-fluorescein group (P = 0.022), especially in patients with tumors in the occipital lobes (P = 0.013). More critically, the gross total resection (GTR) rate was significantly higher in the fluorescein group than in the non-fluorescein group (45.9% vs. 19.6%, P = 0.003). The postoperative residual tumor volume (PRTV) was also significantly lower in the fluorescein group than in the non-fluorescein group (0.40 [0.12-7.11] cm3 vs. 4.76 [0.44-11.00] cm3, P = 0.020). Particularly in patients with tumors located in the temporal and occipital lobes (temporal, GTR 47.1% vs. 8.3%, P = 0.026; PRTV 0.23 [0.12-8.97] cm3 vs. 8.35 [4.05-20.59] cm3, P = 0.027; occipital, GTR 75.0% vs. 0.0%, P = 0.005; PRTV 0.15 [0.13-1.50] cm3 vs. 6.58 [3.70-18.79] cm3, P = 0.005). However, the two groups had no significant difference in intraoperative blood loss (P = 0.407) or postoperative complications (P = 0.481). Conclusions: Fluorescein-guided resection of high-grade gliomas using a special operating microscope is a feasible, safe, and convenient technique that significantly improves GTR rates and reduces postoperative residual tumor volume when compared to conventional white light surgery without fluorescein guidance. This technique is particularly advantageous for patients with tumors located in non-verbal, sensory, motor, and cognitive areas such as the temporal and occipital lobes, and does not increase the incidence of postoperative complications.